Perbedaan Kecemasan Ibu Pre Sectio Caesarea Sebelum dan Sesudah Diberikan Aromaterapi Lavender - Eka Yuli Astrini; Ni Wayan Suarniti; Listina Ade Widya Ningtyas (Journal Center of Research Publication in Midwifery and Nursing, 2026)
Background: Pre-cesarean section (CS) anxiety can adversely affect maternal and fetal health. This study evaluates the effect of lavender aromatherapy as a nonpharmacological intervention to reduce maternal anxiety levels prior to a CS procedure. Methodology: This quantitative study used a pre-experimental, one-group pre-test and post-test design without a control group. Conducted at Singasana Regional General Hospital, Tabanan (March–April 2025), the study involved 30 pregnant women selected via purposive sampling. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) and analyzed with a paired t-test (alpha = 0.05). Results: The mean maternal anxiety score decreased significantly from 55.50 before the intervention to 35.56 after. The paired t-test showed a t-value of 29.854 with a p-value of 0.000 (p < 0.05), indicating a statistically significant reduction in anxiety. Conclusions: Lavender aromatherapy significantly reduces maternal anxiety levels before a cesarean section. Its bioactive compounds, linalool and linalyl acetate, modulate central nervous system neurotransmitters, decreasing sympathetic nervous system activation and helping regulate stress and emotional responses